NILAI TEOLOGIS ARSITEKTUR TRADISIONAL MASYARAKAT HINDU DI BALI - I Made Pasek Subawa (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
The traditional architecture of Hindu society in Bali is a blend of material and spiritual dimensions. The combination of these two dimensions form the energy and strength in the building that is created, so, it can give a sense of comfort and quiet in the person who occupy it. In the belief of Balinese, the people of Bali, the process of building construction is not just to build, but it is done by stages and careful lanning, from the selection of good days, the selection of building materials, up to the means of ceremony. The stage is implemented because the building is not only used as a residence, but also used as a place to carry out various ceremonial activities. This is what causes the traditional Balinese architecture has a spiritual value that makes the building has magical power that can make people who occupy it to be comfortable and quiet.